Presenting the Era (Masa) - Aji Dedi Mulawarman (International Journal of Religious and Cultural Studies, 2020)
This article aims to present a concept of era based on the Qur'anic idea of Al-Ashr. At the first presence, era, whether at historical level, or transcending it, has never escape holiness, as time and space where sacred moral act is always present. At the second presence, era is, in essence, holiness as a reality of being, reality of existence, and presence, where the entire range of the past, present and future is no longer important, even lost, but is a reality that is present in the era without era. At the third presence, holiness, on the other hand, must be historical for the task of the public in the name of love for God, which is part of the deepest consciousness of every human being and human relations where the past, present and future move historically in space and time. At the fourth presence, the real man is thus a man who always purifies his soul without pause in the historical space of time, even beyond it. At the fifth presence, the act of “so be it” (kun fayakun) of God exists, time exists throughout the span of time without any preconditions or constructions based on His commandments (namely Ibn Arabi Bipolar Triplisity).